The Influence of Celebrity Endorsers on Shampoo Purchase Decisions Through Brand Image as an Intervening Variable: Study on Clear Women Shampoo - Agustina, Fitria; Tiarawati , Monika (CV ODIS, 2023)
The more intense competition in the advertising sector, companies compete to carry out promotions. In compiling advertisements, companies need to pay attention to the advertising messages that are created in the minds of consumers. Different appeal is needed to attract the attention of their consumers and to bring up a good brand image in the minds of consumers so that it can cause purchase decision of the products advertised. The respondents of this research are women consumers who had seen shampoo Clear Women advertisement with Agnes Monica as a celebrity endorser. This type of research is quantitative research, the sampling technique used is judgmental sampling, a sample of 110 respondents with Path Analysis analysis techniques. The result of the research is that celebrity endorser has a positive effect on a brand image but has a negative effect on purchasing decisions, while the brand image has a positive effect on purchasing decisions.